2010
DOI: 10.1111/j.1469-8749.2010.03796.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and correlates of restless legs syndrome in adolescents

Abstract: ESS Epworth Sleepiness Scale IRLSSG International Restless Legs SyndromeStudy Group PLMS Periodic limb movements in sleep RLS Restless legs syndrome SDQ Strengths and Difficulties Questionnaire AIM The aim of this study was to determine the prevalence and correlates of restless legs syndrome (RLS) in adolescents.METHOD A sleep questionnaire aimed at identifying 'definite' RLS criteria (also including the Strengths and Difficulties Questionnaire and the Epworth Sleepiness Scale) was completed by 3304 high schoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(51 citation statements)
references
References 27 publications
3
45
1
2
Order By: Relevance
“…22 In the present study, univariate analyses showed that participants with symptoms consistent with RLS were more likely to admit to learning problems (14.3%) than those without RLS symptoms (8.0%), although the difference did not reach statistical significance. Potential participants with ADHD were excluded from the initial TuCASA study to avoid the effects of ADHD on home PSGs.…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…22 In the present study, univariate analyses showed that participants with symptoms consistent with RLS were more likely to admit to learning problems (14.3%) than those without RLS symptoms (8.0%), although the difference did not reach statistical significance. Potential participants with ADHD were excluded from the initial TuCASA study to avoid the effects of ADHD on home PSGs.…”
Section: Discussioncontrasting
confidence: 73%
“…6,21 Yilmaz and associates noted that adolescents with RLS were more likely to experience difficulty falling asleep than those adolescents without RLS (47% vs. 32%) and that adolescents with RLS had generally higher Epworth Sleepiness Scale scores. 22 Arbuckle et al noted that 79% of children and adolescents with RLS had problems falling asleep and 70% felt tired or sleepy during the day. 23 However, the direction of the association between EDS and trouble falling asleep cannot be determined in a cross-sectional design.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 The conclusion from all 3 studies is that childhood RLS is a common disorder, and comorbid mental health conditions are being increasingly recognized. [3][4][5] In a case series of 18 children and adolescents who met diagnostic criteria for pediatric RLS, Picchietti and Stevens described other comorbid disorders such as parasomnias in 7 of 18 subjects, attention deficit hyperactivity disorder (ADHD) in 13 of 18 subjects, oppositional defiant disorder in 4 of 18 subjects, anxiety disorders in 6 of 18 subjects, and depression in 5 of 18 subjects. 6 Yilmaz and colleagues also found a high co-occurrence of ADHD symptoms in children with definite RLS.…”
Section: Methodsmentioning
confidence: 99%
“…However, it is noteworthy that there are no studies with level I evidence to guide therapeutic choices of RLS in children. The non-pharmacological treatment consists in improve sleep hygiene: encourage regular physical activity and improve sleep routines in order to avoid sleep deprivation and exacerbating factors such as caffeinated substances 130,131 .…”
Section: Treatmentmentioning
confidence: 99%